Pembelajaran Interaktif Edu-Game Pengenalan Profesi Berbasis Android Pada Siswa Paud - Muhammad Rais; Muhammad Riska (Jurnal Psikologi Pendidikan dan Konseling: Jurnal Kajian Psikologi Pendidikan dan Bimbingan Konseling, 2018)
This research is a second year development research that aims to test the usefulness, accuracy, and feasibility of interactive professional recognition learning application products. The trial subjects were expert groups (learning media and PAUD learning), product user groups (PAUD teachers), and PAUD students. The results showed that application products included in the criteria were very useful, very feasible and very appropriate. This means that the substance of the edu-game profession application that has been developed has met the criteria of useful, proper and appropriate, so that it can be used as a choice of professional learning introduction media for PAUD students. The results of observations of PAUD students during the product user trial stage, obtained information that shows that PAUD students have been able to: 1) find differences in various types of professions, 2) play puzzle games to recognize the profession, and 3) recognize the profession through audio messages and pictures. Thus the interactive learning product application of edu-game profession meets the criteria of acceptable (acceptable) which is useful, feasible, and appropriate, and therefore can be used as an alternative choice of learning media that is fun and challenging for PAUD students in introducing the profession